Evaluation of the Prevention of Transmission from Mother to Child (PMTCT) Program in Antenatal Care Services (ANC) (Case Study Jember District Health Center) - Rosanti, Dwike Primadita; Mudzakir, Abdul Kohar; Taniasari, Nungky (Sean Institute, 2022)
The Health Policy Program to Prevent Mother-to-Child Transmission (PMTCT) has four prongs/activities with various goals. The PMTCT program, which is integrated with antenatal care in a health institution, is evaluated regularly to measure its success in preventing mother-to-child HIV/AIDS transmission. HIV/AIDS, a virus that assaults the immune system, needs attention, prevention, and treatment in Indonesia, especially in areas with high rates of mother-to-child transmission. HIV/AIDS cases increased in Jember Regency, East Java. The number of HIV-positive people in Jember Regency rose to 644 in 2017, including 42 pregnant women. 25–49-year-olds dominate HIV/AIDS. This study evaluated prong 3 of the PMTCT program at six Public Health Centers in Jember Regency and identified input, processes, output, and outcome in accordance with ANC service standards. This mixed-method research with a sequential explanatory design employed a crosssectional research strategy to investigate input, process, output, and outcome in PMTCT prong 3. After that, qualitative study will prove, deepen, and increase quantitative data, specifically the execution of prong 3 of the PMTCT program in antenatal care services at six public health clinics in Jember Regency. This study employed logistic regression and purposive sampling. Meanwhile, for the second phase of research (qualitative research) there were 18 informants (six key informants, six main informants and six additional informants). This study was concluded in April 2020. This study examined inputs (man, money, method, material, machine), process, output, outcome, and PMTCT prong 3 implementation.